On some generalizations of Baer's theorem - Kurdachenko, L.A.; Pypka, A.A. (Carpathian Mathematical Publications, 2014)
In this paper, we obtained new automorphic analogue of Baer's theorem for the case when an arbitrary subgroup $A≤ Aut(G)$ includes a group of inner automorphisms $Inn(G)$ of agroup $G$ and the factor-group $A/Inn(G)$ is co-layer-finite.